2010
DOI: 10.1002/etc.141
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity of fluorotelomer acids to Daphnia magna and Chironomus dilutus

Abstract: Saturated and unsaturated fluorotelomer carboxylic acids (fluorotelomer acids: FTAs) represent important intermediates in the degradation of fluorotelomer alcohols to perfluorinated carboxylic acids (PFCAs). Recent studies have detected FTAs at low concentrations (ng/L) in precipitation and surface waters; however, information regarding chronic toxicity is lacking. The present study assessed the chronic toxicity of the 8:2 saturated fluorotelomer carboxylic acid (8:2 FTCA) to Chironomus dilutus and the 10:2 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…Findings from other studies also show this trend, where females generally had higher concentrations of upstream metabolites (8:2-FTOH, 8:2-fluorotelomer acid, 7:3-FTA, and unsaturated 7:3-FTA) while males had more downstream metabolites (PFOA, perfluorononanoic acid, perfluoroheptanoic acid) [15,36]. Since some studies have found precursor FTAs to be more toxic than PFCAs [[50], [51], [52]], higher concentrations of FTAs in female rodents may be of concern. These different metabolite profiles in males and females are likely primarily due to the major sex difference in the half-life of PFOA.…”
Section: Discussionmentioning
confidence: 74%
“…Findings from other studies also show this trend, where females generally had higher concentrations of upstream metabolites (8:2-FTOH, 8:2-fluorotelomer acid, 7:3-FTA, and unsaturated 7:3-FTA) while males had more downstream metabolites (PFOA, perfluorononanoic acid, perfluoroheptanoic acid) [15,36]. Since some studies have found precursor FTAs to be more toxic than PFCAs [[50], [51], [52]], higher concentrations of FTAs in female rodents may be of concern. These different metabolite profiles in males and females are likely primarily due to the major sex difference in the half-life of PFOA.…”
Section: Discussionmentioning
confidence: 74%
“…The PFAS precursors (e.g., FTOH, FASAs, FASEs, PAPs) are subject to a variety transformation pathways in the atmosphere or under aerobic and anaerobic conditions in other environmental compartments . Moreover, intermediate degradation products (i.e., FTUALs, FTALs, FTUCAs, FTCAs) formed during both atmospheric transformation and biotransformation are very reactive and have shown acute and chronic toxicity to aquatic invertebrates and green algae . The transport processes of these final degradation products proceed mainly in the water phase but can also occur via seaspray or gas‐phase and particle‐bound transport in the atmosphere .…”
Section: Environmental Fatementioning
confidence: 99%
“…8:2 FTOH and 6:2 FTOH (x ¼ 5) were suggested to induce estrogenic effects in animal models. [19][20][21][22][23] The intermediate metabolites, specically 8:2 FTAL, 8:2 FTUAL, 8:2 FTCA and 8:2 FTUCA, showed higher toxicity than PFAAs in both aquatic organisms 24,25 and human liver epithelial (THLE-2) cells following the order of FTUALs $ FTALs > FTUCAs $ FTCAs > PFAAs. 26 Martin et al found that electrophilic aldehydes and acids were responsible for the depletion of glutathione (GSH) and increased protein carbonylation and lipid peroxidation in isolated rat hepatocytes aer dosing 8:2 FTOH.…”
Section: Introductionmentioning
confidence: 99%